О ТРЕХ МАРКИРУЮЩИХ ПОСТОЯННЫХ ИЗМЕНЧИВОСТИ РАДИАЛЬНОГО ПРИРОСТА СОСНЫ ОБЫКНОВЕННОЙ В БОЛОТНЫХ И СУХОДОЛЬНЫХ ДЕНДРОЦЕНОЗАХ - Ефремов, Станислав; Ефремова, Тамара (Федеральное государственное бюджетное образовательное учреждение высшего профессионального образования "Национальный исследовательский Томский государственный университет", 2011)
Обсуждаются закономерности дифференцированной изменчивости по знакам прироста ширины более 210 тысяч годичных колец у 1333 особей сосны обыкновенной в семи типичных дендроценозах гидроморфного и одном автоморфном рядах развития на междуречье Оби и Томи. Показано, что независимо от типологического и возрастного статуса сосняков общим свойством препарированных хронологий является их согласованная упорядоченность по длине и амплитуде волн в диапазоне 7-11-13-17-летних климатогенно обусловленных циклов. В пределах этих волн пульсируют возрастные частоты меньшей амплитуды и продолжительности, которые имеют в значительной мере не климатогенную, а биологическую и топо-экологическую природу. The regularities of variability differentiated by the signs of growth in width of more than 210,000 tree rings from 1333 specimens of the Scots pine in seven typical dendrocenoses of hydromorphic and automorphic development on the rivers Ob and Tom are described. It is shown that regardless of the typological age and status of a pine, the common feature of prepared chronologies is their coordinated order in length and wave amplitude in the range of 7-11-13-17-year climate conditioned cycles. Within these waves, age frequency of smaller amplitude and duration appear with biological and ecological nature of the topology. It is considered that hydromorphic complexes, being self-regulating natural formations and due to their common conservativeness, have an evident ability to weaken or even suppress the impact of the parameters of the environment, and marsh forest stands against the latter are not sufficiently sensitive. The total dynamics of these properties reflect a weak variation width of tree rings and their small dimensions. Therefore, in this study to decipher the real reactivity of marsh stands the method of sequential accumulation of data on the leading signs of response was used. It allowed to get both theoretically and practically interesting series of prepared chronologies of radial growth for the south-taiga subzone of Western Siberia and on their basis develop a vision of the structure of the hydromorphic and automorphic forest stands reaction to the current variability of the integrated complex of environmental factors. As an example, we give a few random samples from these chronologies for the typical pine forest with a mixed-age stand structure. The study was based on sufficiently large samples, representing every second or third random tree depending on the structure of the tree layer. The graphic comparison of the actual and smoothed data showed that the state of the wetland stands of Western Siberia is characterized by contrasting cyclical swings in relative share of trees with the radial growth positive and negative signs separately. Naturally, they are contrasted to each other, but synchronized in the time of occurrence and duration. Moreover, their reflectivity is shown only to the extent that it may be influenced by the proportion of trees with the zero sign of growth. The cycles contain years-markers, when the proportion of trees with positive or negative effect of the reaction reaches the maximum of 84-87% and the minimum of 4-8% depending on the current combination of climatic factors and environmental confinement of plants. Representation of the neutral form of the response in the swamp forest stands did not exceed 30-32%. For specific forest types, it is practically stable although in general it tends to increase from eutrophic (2-18%) to oligotrophic (12-32%) conditions of growth.